Maximising the nutritional value of microalgae (Chlamydomonas reinhardtii) through cultivation and downstream bioprocessing - Eakpetch, Patchaniya (2019)
Chlamydomonas reinhardtii (C. reinhardtii) has the potential to be a novel food and feed given the range of nutrients and bioactive compounds it contains, but its multilayer cell wall (hydroxyproline-rich glycoprotein [HRPGs]) could restrict the bioaccessibility of its nutrients. Although C. reinhardtii is well characterised, its potential as a functional food/feed ingredient has not been explored. The objectives of the thesis were as follows: (1) investigate the influence of growth media manipulation on the nutritional value of C. reinhardtii; (2) test the impact of mechanical forces on the integrity of C. reinhardtii cells; and (3) measure the impact of a selected cell disruption technique on the bioaccessibility of target nutrients (chlorophyll and carotenoids) in vitro and in vivo digestion. C. reinhardtii was cultivated in a range of media and the nutrients measured. Protein (41.4–43.8%) contains the following amino acids: glutamine, leucine and alanine with trace levels of cysteine, aspartic acid and methionine. Lipid (13.2–20.9%) is comprised of fatty acids (FAs), mostly C16 and C18 in length: α-linolenic acid (C18:3ω3) 5.53 – 27.7% total FAs; palmitic acid (C16:0) 24.5–47.6% total FAs; and oleic acid (C18:1ω9) 8.28–15.7% total FAs. Carbohydrate represents 21.5–27.8% of the dry weight, and the ash comprises 10.1–12.9%. Minerals include calcium (Ca), magnesium (Mg), phosphorus (P), potassium (K) and trace elements (Fe, Cu, Zn, Mn, Mo, Se); this varies depending on the composition of the cultivation medium. C. reinhardtii cells were exposed to two types of mechanical disruption methods. Ultrasonication caused significant cell breakage, with most of the nutrients analysed released from the cells into the external aqueous environment. On the other hand, cells exposed to hydrodynamic cavitation (HDC) retained their overall cellular structure. HDC-treated cells were also more permeable to Nile Red dye, but only a limited portion of nutrients were found in the external aqueous environment. HDC under the condition tested caused some disruption or cell wall breaching, but most of the cells remained intact and retained nutritional content. Any perforations created, as suggested by the dye infiltration, must be small enough to limit the release of nutrients, many of which are associated with subcellular organelles that are,presumably, larger than the pores that appear to have been generated by HDC. This method therefore appears to modify the surface nature of C. reinhardtii. An in vitro model of human digestion was used to measure the bioaccessibility of chlorophylls (a and b) and carotenoids (β-carotene and lutein) from intact and HDC-disrupted C. reinhardtii freeze-dried biomass. The loss of wall integrity by the disruption process led to the more digestible structure but lowered the persistence of nutrients chlorophyll (a and b) and β-carotene. Both intact and HDC-disrupted C. reinhardtii biomass provided a favourable level of lutein bioaccessibility, 34.7 and 34.1%, respectively. Consequently, this finding could pave the way forward to an in vivo assimilation study of lipophilic pigment from C. reinhardtii biomass. In vivo studies showed that growth and other significant parameters for freeze-dried intact C. reinhardtii fed zebrafish were significantly improved compared with fish consuming a standard fish diet. A visible yellow pigmentation of zebrafish (egg in the female and skin in the male) fed with C. reinhardtii only was distinct from the control, which resulted from lutein assimilable. The retinol level in the body of zebrafish increased from 0.5 in the control to 1.85 and 3.5 μg/g at a C. reinhardtii inclusion-level in feed of 10% and 20%, respectively. Thus, it is deduced that zebrafish were able to assimilate β-carotene from C. reinhardtii and convert it to vitamin A.